2012
DOI: 10.14219/jada.archive.2012.0064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the spatter-reduction effectiveness of two dry-field isolation techniques

Abstract: Isolation with a dental dam and HVE or with the Isolite system appears to aid in the reduction of spatter during operative dental procedures, potentially reducing exposure to oral pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 11 publications
1
38
0
1
Order By: Relevance
“…The National Dental Practice-Based Research Network Collaborative Group in the USA reported on the use of a rubber dam during root canal treatment and suggested that improved infection control, patient protection and treatment efficacy were some of the advantages offered by the rubber dam 61 . A significant reduction of spatter during treatments with the application of a combination rubber dam and high-volume evacuation was reported 62 .…”
Section: Focus Area Four: Environmental Barriersmentioning
confidence: 99%
“…The National Dental Practice-Based Research Network Collaborative Group in the USA reported on the use of a rubber dam during root canal treatment and suggested that improved infection control, patient protection and treatment efficacy were some of the advantages offered by the rubber dam 61 . A significant reduction of spatter during treatments with the application of a combination rubber dam and high-volume evacuation was reported 62 .…”
Section: Focus Area Four: Environmental Barriersmentioning
confidence: 99%
“…In addition to cotton rolls and/or gauze, some authors and GDPs claimed that other isolation techniques such as Isolite (Benbrook Dental, USA) are able to enhance visibility, reduce the risk of damage of porcelain surfaces, minimize the risk of perforation and can be useful in young patients with incompletely erupted teeth. 5,30,31 Despite these claims, it is strongly believed that all the above-mentioned clinical situations can be managed with RD application (Table 2). More importantly, such devices will not protect the supporting gingivae from toxic irrigants (e.g.…”
Section: Factors Affecting Rubber Dam Use After Graduationmentioning
confidence: 99%
“…45 In one study uorescent dye was isolated behind a single ply facemask and within the nose of the operator and their assistant. 23 The effect of HVA on dental bio-aerosol is equivocal. An in-vivo study using collection plates noted no statistically signi cant difference in bio-aerosol and spatter reduction between high volume aspiration and saliva ejector.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated dental bio-aerosol properties have been quantitatively and qualitatively evaluated,17, 18, 19, 20 and dental bioaerosol distribution around the operating eld has been appraised. 18,21,22,23,24,25 However whilst these studies have provided invaluable insight into contaminated dental bio-aerosol, they have been unable to ascertain at what point the aerosol has been su ciently dispersed to reduce the health risk to an acceptable level -the 'fallow time'.…”
mentioning
confidence: 99%